PELATIHAN PEMBUATAN VIDEO IKLAN UNTUK PENERAPAN KOMUNIKASI PEMASARAN TERINTEGRASI PADA UMKM KATERING RAYUNG PELANGI KOTA MALANG - Lina Budiarti; Rena Feri Wijayanti; Kun Mustain; Ika Kusumasasti; Kartika Indah Permanasari (Jurnal Pengabdian kepada Masyarakat, 2023)
Marketing is often interpreted narrowly as the activity of distributing products from producers to consumers, even though in fact it is not just that activity. Advertising is one of the many activities in marketing. All activities in marketing need to be integrated with each other so as to produce a mature marketing concept. Likewise with advertising activities which are one of the communication activities in integrated marketing communications. In small businesses, generally communication activities are carried out separately and have not yet integrated their communication activities. This community service aims to provide guidance on the importance of conducting integrated marketing communications, namely integrating marketing communication activities in the form of sales promotions that have already been carried out by partners with advertising.